Design and analysis of a dual-band quad-ridge horn antenna using 3D printing and PLA for wireless communication enhancement performance - Othman, Mohd Azlishah; Adnan, Nur Saqirah; Misran, Mohamad Harris; Said, Maizatul Alice Meor; Jaafar, Abd Shukur; Abd Manap, Redzuan; Suhaimi, Shadia; Hassan, Nurmala Irdawaty (2023)
In this study, we used 3D printing technology to develop and create a quad-ridged horn antenna for use in GSM mid-band and 5G networks. This antenna can function on two different frequencies, 1.8 and 3.5 GHz. Polylactic acid (PLA), a thermoplastic polymer recognised for its outstanding strength and adaptability for 3D printing, was used to create the prototype. The effect of various dimension adjustments on the antenna's performance was studied through a series of parametric experiments. Ridge heights of 3, 4, and 6.25 mm were thoroughly tested. The investigation found that the antenna had a reflection of −16.89 dB at 1.8 GHz and −28.60 dB at 3.5 GHz, proving that it could function at both frequencies with great efficiency. This study proves that 3D printing may be used to create functional prototypes of antennas for use in GSM mid-band and 5G networks. As an added bonus, it stresses the significance of parametric studies in antenna design for peak efficiency.